INTERNET AND MISDEMEANORS FROM THE LAW ON PUBLIC ORDER AND PEACE – MATERIAL LEGAL ASPECTS - Jeličić, Mladen (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In the paper, the author discusses the conditions under which misdemeanor from the Law on Public Order and Peace can be committed via the Internet. These are the existence of the element of publicness, the essential feature of the mentioned misdemeanor, which is manifested through the requirement that the act of execution and the consequences of the misdemeanor be objectified in a public place, and the еligibility of being a misdemeanor. The Internet as a digital space is viewed through two segments: public and non-public Internet space. The criterion of the direction of the enforcement action on public or non-public internet space is defined, which depends on whether the internet can be considered a public place. Spatial, expansive and consequent determination of the public place resulting from the legal definition of this term and the relationship with the Internet were analyzed. Eligibility of being a misdemeanor determines which misdemeanors from the Law on Public Order and Peace can be committed on the Internet. The author’s conclusion is that the focus of the enforcement action on the public Internet space implies the existence of a misdemeanor, and that in the case of a non-public Internet space, the misdemeanor exists if the consequence occurred in a public place or public Internet space.